Punishing the Wicked: Examining the Correlates of Sentence Severity for Convicted Sex Offenders - Rydberg, Jason (Journal of quantitative criminology, 2018)
To examine the correlates of sentence severity for convicted sex offenders under sentencing guidelines, contrasted with individuals convicted of non-sexual, violent offenses.